Memor[ies] of a violent Transition: Analysis of digital initiatives of victims of extreme right-wing and police violence - Aparicio Rodríguez, Víctor; Bueno Aguado, Mario (Hispania Nova, 2021)
Following the rupture of the "hegemonic narrative" of the Transition and the increase in awareness of victims of a political nature, different groups in society have been concerned with recovering the memory of the victims caused by the extreme right or police violence during the process of transition to democracy. In the development of their work, the use of digital resources has become a fundamental tool for these sectors. These virtual spaces appear, on the one hand, as an essential resource to promote the denunciation of the impunity surrounding these events and the demands for truth, justice and reparation defended by these groups and, on the other hand, as a primary source for their study by historiography. This article will analyse the uses and functionalities of different memorial initiatives related to the cases of the 3rd March in Vitoria, the Atocha lawyers, the murder of García Caparrós, the case of the Sanfermines in 1978 and the case of Yolanda González.
Keywords: transition; political violence; victims; impunity; memory; digital resources